2011
DOI: 10.3109/10582452.2011.558996
|View full text |Cite
|
Sign up to set email alerts
|

How Well Does Your Own Pillow Perform?

Abstract: These two papers report on findings from congruent yet separate studies regarding the performance of people's own pillow. Data for these papers was extracted from three previously published studies undertaken in the same South African adult-aged [18+ years] community by the same researchers:1. Study 1: a telephone survey administering a standard questionnaire, and 2. 18 months later, two concurrent experimental studies using five test pillows compared with subjects' "own" pillow: Study 2: a pillow field trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Pillow comfort can also affect sleep quality [ 17 ] because a properly designed pillow allows greater surface contact with the neck, for a more even distribution of pressure on the cervical (neck) muscles [ 18 ]. Although the shape, thickness, and material of commercially available pillows vary, consumers continue to choose based largely on personal preferences [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pillow comfort can also affect sleep quality [ 17 ] because a properly designed pillow allows greater surface contact with the neck, for a more even distribution of pressure on the cervical (neck) muscles [ 18 ]. Although the shape, thickness, and material of commercially available pillows vary, consumers continue to choose based largely on personal preferences [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the shape, thickness, and material of commercially available pillows vary, consumers continue to choose based largely on personal preferences [ 19 ]. However, for the general population, feather pillows may be less performant than those made of other materials [ 17 , 20 ]. Considering that the prevalence of chronic pain ranged from 23.9 to 31.3% in Canadians aged 65 years and older from 1994 to 2008 [ 21 ], studies have examined the use of pillows designed to alleviate cervical pain.…”
Section: Introductionmentioning
confidence: 99%
“…It thus stands to reason that the pillow should be chosen well. The third research study report comes from academic investigators in Queensland and South Australia, Australia (22,23). Their contributions come in the form of two studies reported together in two overlapping papers.…”
Section: Dyscognition In the Fibromyalgia Syndromementioning
confidence: 99%